Projecting Future Transmission of Malaria Under Climate Change Scenarios: Challenges and Research Needs - Yu, W.; Mengersen, K.; Dale, P.; Ye, X.; Guo, Y.; Turner, L.; Wang, X.; Bi, Y.; McBride, W.; Mackenzie, John; Tong, S. (Taylor and Francis Inc., 2015)
There has been an intense debate about climatic impacts on the transmission of malaria. It is vitally important to accurately project future impacts of climate change on malaria to support effective policy-making and intervention activity concerning malaria control and prevention. This paper critically reviewed the published literature and examined both key findings and methodological issues in projecting future impacts of climate change on malaria transmission. A literature search was conducted using the electronic databases MEDLINE, Web of Science, and PubMed. The projected impacts of climate change on malaria transmission were spatially heterogeneous and somewhat inconsistent. The variation in results may be explained by the interaction of climatic factors and malaria transmission cycles, variations in projection frameworks, and uncertainties of future socioecological (including climate) changes. Current knowledge gaps are identified, future research directions are proposed, and public health implications are assessed. Improving the understanding of the dynamic effects of climate on malaria transmission cycles, the advancement of modeling techniques and the incorporation of uncertainties in future socioecological changes are critical factors for projecting the impact of climate change on malaria transmission.